Distribution and species diversity of black flies (Diptera:simuliidae) associated with habitat characterization in Ranau, Sabah - Estherpeni Stephen (2018)
Black flies surveillance studies are still in its infancy in Sabah, as previous studies were limited to discovery of species and taxonomy. This study was conducted to investigate the distribution and species diversity of the black flies in Ranau District. The objectives of this study were (1) to study the distribution and species diversity of black flies in Ranau, (2) to determine the relationship between habitat characterization and distribution of black flies in Ranau and (3) to determine the relationship between micro climate changes on the species and black flies distribution in Ranau. Black flies were sampled every fortnight for a period of 12 months starting from October 2015 to September 2016. Seven study sites were assigned in Ranau District. Sampling of black fly larvae and pupae were manually collected directly from substrates underneath fast flowing water in the streams. A total of 4340 black flies adults were recorded from this study and were classified into subgenus Gomphostilbia, Nevermania and Simulidae. A total of 19 black flies species were identified and among the 19 species, two are newly recorded in Sabah namely; S. alienigenum and S. nobile. While the species S. keningauense and S. sabahense were the common species recorded in all the study sites. The Shannon Weiner’s species diversity index, H’ ranged from 0.45 to 1.68 which indicated low diversity of black flies in all the sites. The species diversity was higher in Kg. Kinarasan with a total of nine species recorded, with the index value, H’ =1.68, while the lowest was in Nikgold area with only four species found and the index value, H’=0.46. The number of black fly pupae and larvae varied depending on the micro climate changes that occurred in Ranau, Sabah. The number of black fly individuals was higher during the rainy season (October – January, June – September 2016) and decreased during the dry season (Febuary – May 2016). The Principle Component Analysis (PCA) results revealed that water temperature, water depth and altitude were the main factors that influence the distribution of black flies species. The linear regression analysis shows that the black flies abundance were significantly associated with the PC-1 which is in lower altitude, wider, deeper, normal temperature, high conductivity, higher velocity and higher dissolve oxygen (F=53.3, df = 1, 4330, P<0.001). As a conclusion, there is a significant relationship between habitat characterization and distribution of black flies in Ranau with the Canonical Correspondence Analysis value was P= 0.002. In addition, the linear regression also shows there is a significant relationship between microclimate changes on the species of black flies abundance in Ranau District (R²=0.131, P<0.01).